Indigencia, migración y locura en el México posrevolucionario - Ríos Molina, Andrés (El Colegio de México, A.C., 2010)
During the first ten years of operation, the general Asylum La Castañeda (1910-1920) received an average 601 patients per year, but after 1920 the number increased considerably. This work analyzes the factors determining the rise in psychiatric patients between 1920 and 1944. The author demonstrates how two main issues influenced this process: anti-poverty campaigns carried out by Mexico City authorities during  the 1930's, and heavy migration  from the countryside combined with the repatriation of Mexican workers from the United States.